Prevalence of Chronic Kidney Disease and Its Association with Risk Factors in Disadvantageous Population - Md Nurul Huda; Kazi Shahnoor Alam; Harun-Ur-Rashid (International Journal of Nephrology)
The prevalence of kidney disease, particularly diabetic and hypertensive kidney disease is increasing rapidly specially in the disadvantageous group of population throughout the world. A cross sectional survey was carried out at certain selected slum areas of Mirpur in Dhaka city of Bangladesh over the period from July 2003 to June 2005, and a total of participants ranging from 15 to 65 years were studied. The analysis discovered that 4.1% of the participants were diabetic, 11.6% were hypertensive, and 7.7% had proteinuria. Based on MDRD equation, 13.1% of the participants were detected as having chronic kidney disease (CKD) while with Cockcroft-Gault equation 16% had CKD. Accordingly, the difference between the two equations was not significant. Association of sociodemographic factors with CKD was not significant except age more than 40 years and marital status. The association between CKD and risk factors like proteinuria, obese and overweight, use of tobacco, diabetes mellitus, and hypertension was highly significant. Combined prevalence of DM, hypertension, and proteinuria among CKD group was also demonstrated to be significantly higher (3.8% with Cockcroft-Gault equation and 5.3% with MDRD equation) than that of normal population. The survey data revealed that CKD and its risk factors like DM and hypertension are alarmingly high in disadvantageous population and adding further pressure to the existing burden of CKD.